GAMBARAN HASIL PEMERIKSAAN LEUKOSIT URINE MENGGUNAKAN METODE MIKROSKOPIK DENGAN ALAT AUTOMATIK MEDITRON JUNIOR - Nismawati Natrsir; Sri Rahayu Ilyas; Husain Abdullah (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2019)
Microscopic examination of breathless urine to determine the presence of abnormalities in the kidneys and urinary tract. The urine used is urine needed. Sediment experiments are carried out using an objective (10X) called the small visual field or LPK. Besides that, objective (40X) which is called the big field of vision or LPB is also used. This study is motivated by researchers intending to conduct research on the massive assessment of leukocytes in the urine using microscopic methods with automatic tools. Having conducted research aimed at studying the results of microscopic leukocyte examination of microscopic methods with these automatic devices, use laboratory observational methods. The results of the study on 20 samples obtained were all normal. Conclusions Based on the results of the study showed the results of urine leukocyte examination using microscopic methods with automatic devices obtained the results were all normal. It is necessary to be able to use other examinations to complete data on various examination methods in order for researchers to provide accurate and more accurate examination results.